Wedge-Shaped Beetles (suggested common name) Ripiphorus spp. (Insecta: Coleoptera: Ripiphoridae) - David Owens; Ashley N. Mortensen; Jeanette Klopchin; William Kern; Jamie D. Ellis (EDIS)
Ripiphoridae are a family of unusual parasitic beetles that are thought to be related to tumbling flower beetles and blister beetles. They parasitize bees and wasps, roaches, and wood-boring beetles, but specific hosts for many ripiphorid species are unknown. Their secretive life cycle makes an assessment of their economic and ecological impact very difficult. Additional research is necessary to determine the abundance and impact of Ripiphorus species. This 4-page fact sheet was written by David Owens, Ashley N. Mortensen, Jeanette Klopchin, William Kern, and Jamie D. Ellis, and published by the UF Department of Entomology and Nematology, December 2014.